Sea Surface Topography and the Geoid Edinburgh, Scotland, August 10?11, 1989 - Snkel, Hans; Baker, Trevor (International Association of Geodesy Symposia, 1990)
Recent advances and techniques in precise geoid determination are presented with a discussion of their implication for geophysical and oceanographic research, as well as identification and formulation of a goal on which future geoid research should focus. The volume is divided into the following sections: - The Geoid - Sea Surface Topography - The Vertical Datum - Miscellaneous